Food processing the baking of bread - Satterlee, Lowell D. (Penn Media Sales, 1992)
Discusses the bread-making method known as batch processing. Covers the production of the hard-crusted, soft-crumb dinner roll: the combination of dry and liquid ingredients, mixing, shaping, proofing, baking, cooling, and the final packaging of the rolls.